2018
DOI: 10.1111/1753-0407.12795
|View full text |Cite
|
Sign up to set email alerts
|

N‐Acetylcysteine alleviates gut dysbiosis and glucose metabolic disorder in high‐fat diet‐fed mice

Abstract: N-Acetylcysteine may be a potential drug to prevent glucose metabolic disturbances by reshaping the structure of the gut microbiota.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 45 publications
1
38
0
Order By: Relevance
“…It was interesting that, when supplemented with NAC, there was a reduction in the fasting blood glucose and an increase in insulin sensitivity. Zheng et al, (23) administered NAC orally in the drinking water for 5 months showed similar results. Obese mice that received NAC for 5 months had an improvement in fasting blood glucose and higher glucose tolerance, which reinforces the involvement of oxidative stress in the pathophysiology of insulin resistance.…”
Section: ❚ Discussionmentioning
confidence: 73%
“…It was interesting that, when supplemented with NAC, there was a reduction in the fasting blood glucose and an increase in insulin sensitivity. Zheng et al, (23) administered NAC orally in the drinking water for 5 months showed similar results. Obese mice that received NAC for 5 months had an improvement in fasting blood glucose and higher glucose tolerance, which reinforces the involvement of oxidative stress in the pathophysiology of insulin resistance.…”
Section: ❚ Discussionmentioning
confidence: 73%
“…Allobaculum is a beneficial intestinal bacterium [57,58] that produces lactic and butyric acids and small amounts of ethanol from glucose [57] and decreases glucose digestion [59]. Several studies have correlated increased abundance of Allobaculum with a lean phenotype [60] and glucose tolerance [61]. S24-7, a dominant family belonging to the class Bacteroidales, degrades complex polysaccharides into acetate, propionate, and succinate [62].…”
Section: Discussionmentioning
confidence: 99%
“…Allobaculum is a putative beneficial bacteria able to produce short‐chain fatty acid (SCFA), which are shown to deliver multiple systemic and targeted benefits to the mammalian host. Several studies reported that Allobaculum genus was selectively enriched when mice were treated with berberine, calorie restriction or N‐acetyl cysteine to reduce weight gain or to improve metabolism. Also, a recent study reported Allobaculum , together with Lactobacillus , Candidatus Arthromitus , segmented filamentous bacteria were four dominant candidate protective taxa in young mice.…”
Section: Discussionmentioning
confidence: 99%